Preliminary Pharmacognosy Evaluation of The Bark of Acacia Catechu (Wild.) - ram, Sukha; Sharma, Ritu; Kotecha, Mita; Chaudhary, Krutika (International Research Journal of Ayurveda & Yoga, 2021)
Khadira (Acacia catechu Wild, family: Fabaceae and subfamily: Mimosoideae), is considered as one of the most potent medicine used for various skin diseases in Ayurveda. It is widely used herb in Indian traditional system of medicine. The sample of Acacia catechu (Wild.) bark (Khadira Tvaka) collected from market. The diagnostic characters of bark of this plant include astringent and bitterin taste, odourless, light brown or brownin colour, Tracheid, Fiber, Calcium oxalate crystals and Starch grains. Physicochemical studies revealed moisture content (2.88%), pH value (5.6), alcohol (3.00%) and water soluble extractive value (3.09%), total ash (1.24%), acid insoluble (0.34%) and water soluble ash (0.89%). Preliminary analysis of various functional groups revealed the presence of carbohydrate, alkaloids, amino acids, protein, saponin, phenolic compound, tannins and Thin Layer Chromatography (TLC) etc. The information generated by this particular study will provide relevant Pharmacognostical and physicochemical data needed for proper identification, authentication, purity, safety and efficacy of the drug.